Tuberculosis y una Gemella spp: Una combinación indeseable - Alberto Fernando Buitrago-Gutiérrez (Asociación Colombiana de Infectología, 2020)
Gemella spp. corresponds to gram positive cocci, facultative anaerobes, negative catalase, non mobile and non spore producers, part of colonizing flora of the oral cavity that are not common pathogens in immunocompetent patients. Nevertheless it may behave as an opportunistic germ in immunosuppressed patients or with other risk factors that include bad dental hygiene, bowel surgery, and metabolic diseases among others. It's associated with infections such as endocarditis, meningitis and less frecuently can implicate the lung. The information regarding antimicrobial susceptibility is limited and resembles S viridans, so penicillin and ampicillin are the medications of choice, without being clear about the duration of treatment, usually giving 4 weeks or until collection drain. This case report describes a patient with known tuberculosis diagnosis and under treatment, that develops an invasive infection with empyema and secondary bloodstream infection by Gemella morbillorum, depicting a previously uncommon but described association of this bacterial infection with tuberculosis.